Camus and Rousseau: freedom, justice and 'the despotism of the general will'. Issue 5 (4th July 2022) - Foley, John
ABSTRACT: Despite being generally recognised as Camus' most important philosophical essay, L'Homme révolté (1951;trans. The Rebel, 1953/1954, rev.1956) is rather neglected in the scholarship and enjoys a limited readership, especially among Anglophone critics and readers – a fact brightly reflected in the questionable quality of the only English translation, by Anthony Bower, and in the decision of Hamish Hamilton and Penguin, Camus' publishers in the UK, to cut about thirty pages of text from their edition, 'in the interests of economy.' (This startling admission, hidden in a footnote to Herbert Read's Introduction in 1953, disappeared from the Penguin edition in 2000, though the textual excisions remain). This essay examines one brief but crucially important section of L'Homme révolté concerned with Rousseau's Du contrat social (1762). It explores the centrality of Camus' analysis of Rousseau's essay and its influence on the French Revolution to the arguments of L'Homme révolté, especially as these pertain to political or revolutionary violence. It also examines in close detail some striking parallels between Camus' analysis of Rousseau and that found in essays by Isaiah Berlin (1952) and Philip Pettit (2016).